Animal testing for vaccines. Implementing replacement, reduction and refinement: challenges and priorities. (November 2020) - Akkermans, Arnoud; Chapsal, Jean-Michel; Coccia, Eliana M.; Depraetere, Hilde; Dierick, Jean-François; Duangkhae, Parichat; Goel, Sunil; Halder, Marlies; Hendriksen, Coenraad; Levis, Robin; Pinyosukhee, Koraphong; Pullirsch, Dieter; et al.
Abstract: Transition to in vitro alternative methods from in vivo in vaccine release testing and characterization, the implementation of the consistency approach, and a drive towards international harmonization of regulatory requirements are most pressing needs in the field of vaccines. It is critical for global vaccine community to work together to secure effective progress towards animal welfare and to ensure that vaccines of ever higher quality can reach the populations in need in the shortest possible timeframe. Advancements in the field, case studies, and experiences from Low and Middle Income Countries (LMIC) were the topics discussed by an international gathering of experts during a recent conference titled " Animal Testing for Vaccines – Implementing Replacement, Reduction and Refinement: Challenges and Priorities ". This conference was organized by the International Alliance for Biological Standardization (IABS), and held in Bangkok, Thailand on December 3 and 4 2019. Participants comprised stakeholders from many parts of the world, including vaccine developers, manufacturers and regulators from Asia, Europe, North America, Australia and New Zealand. In interactive workshops and vibrant panel discussions, the attendees worked together to identify the remaining barriers to validation, acceptance and implementation of alternative methods, and how harmonization could be promoted, especially for LMICs. Highlights: Update on the current status of vaccines reduce, replace and refine opportunities. Update on the drivers and barriers identified for the validation, acceptance and implementation of alternative methods. Update on the drivers and barriers identified for the implementation of 3Rs in developing countries. Propose a way forward for the global implementation of 3Rs in the vaccines' area.